The Influence of Accountability and Transparency on the Quality of Public Services of the Investment and One-Stop Integrated Licensing Service Office of Binjai City - Ardia Theresia Br Pasaribu; Galih Supraja (International Journal of Economic Research and Financial Accounting, 2025)
This study is entitled "The Influence of Accountability and Transparency on the Quality of Public Services of the Investment and One-Stop Integrated Licensing Service in Binjai City". This study aims to analyze the influence of Accountability and transparency on the Quality of Public Services. This study uses a descriptive research approach. Data collection techniques in this study use questionnaires that have been tested instrumented. The population in the study were visitors at the research location in 2024 as many as 135 people and 57 were sampled using the Slovin formula while the technique used was random sampling. The data analysis technique used multiple linear regression with the Statistical Package for Social Science (SPSS) program. The results of this study indicate that 1) there is a positive and sig influence of Accountability on the Quality of Public Services 2) there is a positive and sig influence of transparency on the Quality of Public Services, 3) there is a positive and sig influence of Accountability and Transparency on the Quality of Public Services while for the contribution of independent variables to the Quality of Public Services is a contribution of 70.5%, while the remaining 29.5% is influenced by other variables.